Brain Dystrophin in Duchenne Dystrophy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
To define the potential pathogenic role of dystrophin deficiency in the cognitive impairment characteristic of Duchenne muscular dystrophy (DMD), the protein in brain cortical synapses of an 8-year-old patient examined at autopsy and an age-matched control subject dying of myelogenous leukemia was analysed in the Department of Neuroscience and Cell Biology, Rutgers-The State University of New Jersey, Piscataway, NJ.